Analisis Posisi Keuangan PT. Unilever Pada Industri Produk Rumah Tangga Periode 2019-2021 - Budi Dharma; Selvira Wardani Tanjung; Reni Yusnita (LPPM Universitas Labuhanbatu, 2023)
The purpose of this research is to conduct an analysis process on the financial performance of PT Unilever Indonesia, Tbk during the period 2019-2021 which is assessed based on the ratio of solvency, liquidity, activity, and profitability, by applying several financial ratio techniques. In terms of liquidity ratios, debt-to-assets and capital ratios, as well as its activities, this company is classified as â€œnot goodâ€, because the average value generated in the last three years is below the average of other companies in general. While the total asset turnover ratio shows a value that is classified as